Examining University Student Perception of Romance Relationship - Lukman@Zawawi, Mohamad; Normala, Riza; Azlini, Chik (2018)
Nowadays, we often come across teenagers who are involved in romantic relationships. During adolescence, teenagers are more prone to be involved in a romantic relationship. There are various perceptions expressed by each individual in their romantic relationship. The study is conducted to determine the perception of the romantic relationship among university students. The researcher conducted a study by obtaining data through the participation of University Sultan Zainal Abidin's students and 351 respondents had answered the questionnaire given. Respondents consisted of 124 male students and 227 female students. A total of 88.0% of the respondents stated that they love their partner and 82.4% stated they were serious about their love affair. In conclusion, most of the students show that they love their partner and serious on the love affair they had in university life.